Makna Rasa Memiliki terhadap Komunitas di Kalangan Anggota Jazwa: Studi Fenomenologis - Salma Novia Nurfarida; Hilwa Junaida Fairuz; Anita Rosita Dewi Indriani; Hilla Zahrotul Habibah; Siti Hikmah (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study explores the lived experiences of Jazwa community members to understand how their sense of belonging is formed and sustained through dynamic interpersonal and spiritual processes. Using a phenomenological approach, the research investigates four core dimensions membership, influence, integration, and shared emotional connection as conceptualized in classic community psychology theory. Data were collected through in-depth interviews and participant observations, allowing the voices of members to reveal how social recognition, collaborative engagement, and collective spiritual activities shape their emotional attachment to the community. Findings show that belonging emerges not merely from formal organizational structures but from the accumulation of meaningful interactions that foster emotional security, mutual trust, and continuity of relationships. Members describe feeling valued, needed, and emotionally connected through shared challenges and rituals, which strengthen their commitment to ongoing involvement. This study highlights the role of spiritual-based communities in providing psychosocial support and identity affirmation, offering insight into how contemporary youth communities construct resilient emotional bonds that contribute to long-term social well-being.